The role of emotion regulation and empathy in students displaying cyberbullying - Mujidin, Mujidin; Nuryoto, Sartini; Rustam, Husnul Khotimah; Hildaratri, Alifiana; Echoh, Daniel Ugih (Humanitas: Indonesian Psychological Journal, 2023)
Anxiety, anger, sadness, and other negative emotions are the harmful effect of bullying, especially in today's digital era. Many cases of bullying happen through social media, often associated with cyberbullying. Therefore, cyberbullying is increasingly common and requires control as early as possible. This study aims to identify the role of students’ emotion regulation and empathy in cyberbullying behavior. The participants are 64 university students who tend to commit cyberbullying, chosen with the cluster random sampling technique. Three measurement tools, cyberbullying scale, emotion regulation scale, and empathy scale, were used in this study. Data were then analyzed with multiple linear regression analysis. Our finding reveals that emotion regulation significantly predicts cyberbullying, but empathy is not predicting cyberbullying. Emotion regulation allows students to keep their composure, control their words and action according to prevailing customs and norms and avoid showing aggression to people. Emotion regulation can help students to break the chain of cyberbullying.